Regional Assessment of the Seagrass Ruppia maritima L. in the Tropical Atlantic Seagrass Bioregion (Bioregion 2) for the IUCN Red List - Frade, Duarte Gonçalves (2025)
This assessment is one of 15 individual regional species assessments prepared by the IUCN Species Survival Commission (SSC) Seagrass Species Specialist Group (SSSG) Members (Jimena Samper-Villarreal (regional leader), Brigitta I. van Tussenbroek, Joel C. Creed, Bradley Furman, Duarte Frade, Ester A. Serrão, Hacen Mohamed El-Hacen, Salomão Bandeira, Ana Carolina Peralta, Beatriz Esther Vera Vegas and Kathryn Coates) for seagrasses which occur in the Tropical Atlantic Seagrass Bioregion (Bioregion 2). As part of the IUCN Global Assessment of Seagrass Extinction Risk, the Tropical Atlantic Bioregion carried out the assessments between June 2020 and July 2021. Preliminary assessments were submitted for review to the IUCN SSC SSSG Leadership Team (Fred Short & Brooke Sullivan) between November 2020 and July 2021. Feedback for each assessment was provided by the Leadership Team between June and September 2021. Final assessments were submitted to the Leadership Team between July 2021 and February 2022 for publication. Additionally, detailed mapping and spatial considerations for each were sent to the Leadership Team between February 2021 and January 2024. These regional assessments considered the assessment time period between 2007 and 2020 and applied standard guidelines for using the IUCN Red List Categories and Criteria on all species which occurred in the bioregion, except non-native species. The assessed status should be considered regional for the six species which are native to more than one seagrass bioregion and both regional and global for the ten species which only occurred in the Tropical Atlantic Seagrass Bioregion. This assessment is accompanied by the shapefiles used to assess the geographical distribution of the species in the bioregion.